Pasantía En La Oficina De La Secretaría De Infraestructura De La Alcaldía Municipal De Santa Rosa Del Sur, Bolívar (2024)
This document presents a report related to the development of the business practice that will be carried out during the period from August 5, 2024 to November 15, 2024, as an assistant engineer in the infrastructure secretariat of the municipal mayor's office of Santa Rosa del Sur, carrying out support activities in the supervision of the different sewerage works that are being carried out in the municipality of Santa Rosa del Sur. The practice is developed through field visits in which work supervision is carried out, balances of larger and smaller quantities of work, control of materials, socializations with the community; administrative part consisting of the preparation of supervision reports, projection of suspension minutes, restart of works, etc.